Magnitude - Seddon, Deborah Ann (Rhodes University, Faculty of Humanities, School of Languages and Literatures)
My thesis is a collection of lyric, narrative, and prose poetry directed towards two forms of death "“ physical death and the disavowal of the self. Many poems focus on the death of my mother, and the work required after loss to sort through a family's life in my Harare childhood home. This associative exploration draws together childhood memories, encounters with physical objects, letters, and songs, as well as with the city and its people. Tadeusz RÃ³zewicz's Mother Departs has influenced my approach to writing of my mother's death, particularly how to grant her a voice in the telling. I also draw on the poetry of Harmony Holiday and Pascal Petite, in their attention to the complexities and emotional dangers of the mother-daughter bond. Other poems draw on the work of Adrienne Rich, Audre Lorde, Judy Grahn, Ocean Vuong, and Saeed Jones, in terms of imagining queer life into poetry, the use of the erotic as a means of empowerment, and developing a queer political identity, to examine various aspects of queer love, including the heartaches associated with self-denial.
Keywords: Creative writing (Higher education) -- South Africa; Zimbabwean poetry (English) 21st century; Diaries -- Authorship; Polish literature 21st century History and criticism; English poetry 20th century History and criticism; English literature Irish authors History and criticism; American poetry 21st century History and criticism